Communication as a Pillar of Educational Administration: Challenges and Solutions in the Digital Era - Lingga Karunia Ilahi; Raffly Gilang Ramadhan (Amandemen: Journal of Learning, Teaching and Educational Studies, 2025)
Educational administration is a crucial element in the success of the education system, serving to manage human and material resources to achieve educational goals. In the digital era, communication challenges in educational administration have become increasingly complex due to the digital divide, resistance to change, and the need for data security and privacy. This study aims to explore communication challenges in educational administration in the digital era and propose strategies to overcome these barriers. The approach used is a literature study with inductive analysis of relevant literature. The research findings indicate that the digital divide, information complexity, and resistance to change are the main obstacles in educational communication. Additionally, the use of digital platforms poses data security risks that require special attention. The proposed strategies include developing digital competencies through training, utilizing effective communication platforms, implementing data security policies, and fostering a culture of open communication. By applying these strategies, educational institutions are expected to optimize digital communication to support the success of educational administration in the modern era.